2012
DOI: 10.1111/j.1600-0404.2011.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T2′ imaging in patients with clinically isolated syndrome

Abstract: Objective T2′ imaging has been shown to be sensitive to oxygen saturation changes in normal appearing white and grey matter (NAWM, NAGM) in patients with relapsing-remitting multiple sclerosis (RRMS). We aimed to explore the presence and extent of T2′ changes in patients with a clinically isolated syndrome (CIS) and a possible association of T2′ with conventional MRI and clinical outcomes. Material & methods Quantitative T2- and T2*-weighted images were acquired in 32 treatment-naive patients with a CIS with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Patients of male gender, with efferent lesions, multifocal presentation, incomplete remission, and high relapse rate in the first 5 years after onset have a worse prognosis . To a lesser extent, the number of baseline brain MRI lesions and the rate of lesion load increase in the short term predict the likelihood of developing subsequent disability . Additionally, some studies suggest that evoked potentials (EPs) abnormalities predict poor recovery and disability progression after a CIS .…”
Section: Introductionmentioning
confidence: 99%
“…Patients of male gender, with efferent lesions, multifocal presentation, incomplete remission, and high relapse rate in the first 5 years after onset have a worse prognosis . To a lesser extent, the number of baseline brain MRI lesions and the rate of lesion load increase in the short term predict the likelihood of developing subsequent disability . Additionally, some studies suggest that evoked potentials (EPs) abnormalities predict poor recovery and disability progression after a CIS .…”
Section: Introductionmentioning
confidence: 99%
“…There are again mixed results with diffusion based measures, with some studies finding changes (48)(49)(50) and others not (51,52), sometimes even for the same measures. Another study has shown no change in T 2 ′ (possibly related to oxygenation) in CIS (53), but another has noted a reduction in NAWM perfusion (54). To the best of our knowledge, this is the first study that investigates the T 1 relaxation time along with MTR at both offsets in NAWM of the CIS patient for ultrahigh field MRI.…”
Section: Relation To Other Workmentioning
confidence: 87%